Sistem Informasi Pendataan Anggota Partai Gelombang Rakyat Indonesia Kabupaten Lampung Utara - Gunawan Adi Saputra; Khusnul Khotimah (Riset Sinergi Indonesia (RISINDO), 2026)
This research aims to develop an information system for the membership data of the Indonesian Wave of the People Party (Gelora) in North Lampung Regency. The system is designed to address the challenges of manual member data management, which often leads to data duplication, errors, and difficulties in reporting. The study adopts a descriptive qualitative method with a structured waterfall development model. The development process includes requirements analysis, system design, implementation, and testing. Data was collected through three main techniques: (1) direct observation of the ongoing member data collection process at the party office; (2) interviews with party officials and administrative staff to identify specific needs, workflows, and existing problems; and (3) a literature review to examine concepts, theories, and references related to information system development and data management. The result of this research is a web-based information system that allows party officials to centrally record members' data, manage member profiles, and automatically generate membership reports. Key features include new member registration, data updates, data search, and comprehensive reporting. System testing showed that the application functions well, is valid, and is highly effective in improving the efficiency, accuracy, and transparency of membership data management for the Gelora Party in North Lampung Regency.